(untitled) (Journal of the College of Basic Education, 2024)
The research focuses on the role of digital imagery in achieving brand transformations in fashion fabric designs and meeting the preferences of the recipients. It targets an age group between )25 . 30 (years old and includes women’s evening fashion fabric designs of Chinese origin. The study analyzes design patterns and the use of digital imagery, with a specific emphasis on colors and space. The results highlight the importance of using dark colors and space in fabric designs, as well as the impact of incorporating natural elements in the design process. The research also provides recommendations and proposals based on the findings.